2016
DOI: 10.2147/dddt.s103829
|View full text |Cite|
|
Sign up to set email alerts
|

Ursolic acid reduces the metalloprotease/anti-metalloprotease imbalance in cerebral ischemia and reperfusion injury

Abstract: BackgroundActivators of PPARs, particularly PPARγ, may be effective neuroprotective drugs against inflammatory responses in cerebral ischemia and reperfusion injury. Ursolic acid (UA) may act as a PPARγ agonist and serve as an anti-inflammatory agent. In this study, we used a rat middle cerebral artery occlusion and reperfusion model to examine how UA acts as a neuroprotective agent to modulate the metalloprotease/anti-metalloprotease balance.MethodsThe middle cerebral artery occlusion and reperfusion model (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 43 publications
4
20
0
Order By: Relevance
“…This occurs because UA could suppress the NF-kB-dependent pathways that are activated by tumor necrosis factor-alpha (TNF-α) or interleukin 1 beta (IL-1β). Similar results were obtained by Wang et al [ 20 ], who revealed the association between UA and MMP-2/-9 expression in a rat model of cerebral ischemia and reperfusion injury. In this study, the activities of MMP-2 and MMP-9 were suppressed by UA administration.…”
Section: Effects Of Ua On Brainsupporting
confidence: 91%
See 1 more Smart Citation
“…This occurs because UA could suppress the NF-kB-dependent pathways that are activated by tumor necrosis factor-alpha (TNF-α) or interleukin 1 beta (IL-1β). Similar results were obtained by Wang et al [ 20 ], who revealed the association between UA and MMP-2/-9 expression in a rat model of cerebral ischemia and reperfusion injury. In this study, the activities of MMP-2 and MMP-9 were suppressed by UA administration.…”
Section: Effects Of Ua On Brainsupporting
confidence: 91%
“…UA is isolated from the leaves of various plants (rosemary, marjoram, lavender, thyme, and organum), fruits (apple fruit peel), flowers, and berries [ 11 ]. UA mediates some pharmacological processes and modulates several signaling pathways to prevent the development of chronic diseases [ 12 13 ]; it exhibits antiinflammatory [ 14 ], anti-oxidant [ 15 ], anti-carcinogenic [ 16 ], antiobesity [ 17 ], anti-diabetic [ 18 ], cardioprotective [ 19 ], neuroprotective [ 20 ], hepatoprotective [ 21 ], anti-skeletal muscle atrophy [ 22 ], and thermogenic effects [ 8 ]. The mechanisms by which UA exerts these beneficial effects may involve regulation of the following: nuclear factor-kappa B (NF-kB) and apoptotic signaling in cancer cells, insulin signaling in adipose tissue, the expression of markers of cardiac damage in the heart, inflammation and the level of anti-oxidants in the brain, metabolic signaling and the level of oxidants in the liver, and atrophy signaling and metabolic signaling in skeletal muscles.…”
Section: Introductionmentioning
confidence: 99%
“…at doses of 10 and 20 mg/kg. This finding provides further evidence that UA could be an effective therapeutic agent for cerebral ischemia ( 17 , 33 ). Our findings provide new insights into the potential effects of UA on brain ischemia.…”
Section: Discussionsupporting
confidence: 61%
“…when the other treatment groups were administered UA or GL. (3) In the low-dose UA (L-UA) group ( n = 18), 10 mg/kg UA (purity ≥ 95.0%, Sigma-Aldrich, St. Louis, MO, USA) in distilled water containing 0.5% Tween-80 (ddH 2 O/0.5% Tween-80) was administered by oral gavage at 0.5, 24, and 47 h after reperfusion, according to previous studies clarifying the oral absorption rate and drug action time ( 15 17 ). (4) The high-dose UA (H-UA) group ( n = 18) was administered 20 mg/kg UA.…”
Section: Methodsmentioning
confidence: 99%
“…In a subarachnoid hemorrhage rat model, UA treatment reduced early brain injury via reducing apoptosis and suppressing TLR4-mediated inflammatory factors, such as intercellular adhesion molecule-1 (ICAM-1), TLR4, NF-κB, IL-1β, TNF-α, IL-6, iNOS, and matrix metalloproteinase (MMP)-9 [127]. It also showed neuroprotective effects as an activator of PPARs in a rat model of cerebral artery occlusion and reperfusion and modulated the metalloprotease/anti-metalloprotease balance, possibly by inhibiting the MAPK signaling pathway [128]. UA has also been shown to have anxiolytic, anticonvulsant, and antidepressant activities in mice via affecting the GABA-A receptor, especially acting on the benzodiazepine binding site of GABA receptors [129,130].…”
Section: Ursolic Acidmentioning
confidence: 99%